(3GdfXe GdSjGSjI (B:s (3GdSdWI, GdOhdI, GdMcheI UhQgG hCSGdjHgG GdGfJNGHGJ CfhGYgG hJfXjegG GdMbhb hGdMQjGJ GdYGeI (B/s - (3eJhdj, QHjY CfhQ aJM GdHGHs ((3HjQhJ (B:s (3efThQGJ GdMdHj GdMbhbjI,s, 2013)
(3jJMOK GdcJGH Yf GdfXe GdSjGSjI MjK Ef GdfXe GdSjGSjI HGdJYQja gj eLehYI GdeHGOF hGdbhGYO GdJj JJYdb HTcd GdMce aj GdOhdI hHGdSdWGJ GdeNhdI dgjFGJgG GdSjGSjI hdCLgRJgG GdEOGQjI hHcjajI eHGTQJgG dGNJUGUGJgG hYdGbGJgG HGdehGWfjf hHMbhb hGdJRGeGJ GdCaQGO JLGg GdOhdI hGfWdGbG ef gPG GdJYQja jHMK eDda GdcJGH aj GdLhGfH GdfXQjI hGdbGfhfjI ddfXe GdSjGSjI hPdc HGSJYQGV GdCacGQ GdeNJdaI aj eTcdI GdSdWI Ke GdYfGUQ GdeNJdaI ddCfXeI GdSjGSjI hJYQja GdOhdI hCQcGfgG hhXGFagG hGdMcheI hCfhGYgG hWQb GNJjGQgG hUhQgG hcjajI ESfGO GdSdWI EdjgG Ke GdMbhb hGdMQjGJ GdYGeI(B.s
Keywords: (3GdYdhe GdSjGSjIs; (3GdfXe GdSjGSjIs; (3GdSdWI GdSjGSjIs